2016
DOI: 10.1159/000444222
|View full text |Cite
|
Sign up to set email alerts
|

NaF Inhibits Matrix-Bound Cathepsin-Mediated Dentin Matrix Degradation

Abstract: Matrix metalloproteinases (MMPs) and cysteine cathepsins (CCs) degrade the collagen fibrils of demineralized dentin. Sodium fluoride (NaF) has previously been shown to inhibit recombinant MMP-2 and MMP-9. This study aimed to evaluate the efficacy of NaF on the inhibition of dentin-bound MMPs and CCs. Dentin beams were completely demineralized in 10% phosphoric acid. The baseline total MMP activity and dry masses were measured. Beams were assigned to test groups based on similar MMP activity and dry mass (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
3
25
1
Order By: Relevance
“…It should be noted that the immersion of EDTA-demineralized dentin in artificial saliva for up to several days or weeks did not induce remineralization [31][32][33] . On the other hand, there is a study revealed that demineralized dentin immersed in artificial saliva for up to 21 days showed constant (slight) activity of endogenous collagenases, comparing to 1-day immersion 34) . Therefore, it could be assumed that activity of endogenous collagenases would be minimum and the properties of collagen in 24-h immersion of Control group would not be different from 30-s immersion.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that the immersion of EDTA-demineralized dentin in artificial saliva for up to several days or weeks did not induce remineralization [31][32][33] . On the other hand, there is a study revealed that demineralized dentin immersed in artificial saliva for up to 21 days showed constant (slight) activity of endogenous collagenases, comparing to 1-day immersion 34) . Therefore, it could be assumed that activity of endogenous collagenases would be minimum and the properties of collagen in 24-h immersion of Control group would not be different from 30-s immersion.…”
Section: Discussionmentioning
confidence: 98%
“…These phenomena happen in parallel with a continuous degradation of dentin matrix by bacterial and host-derived proteases. In vitro demineralized dentin matrix can be self-degraded by endogenous matrix-embedded proteases without the presence of bacteria [Brackett et al, 2015;Seseogullari-Dirihan et al, 2015;Altinci et al, 2016]; however, in in vivo dentin caries, bacteria are always present, at least in the infected layer of the carious dentin, and inevitably contribute to further degradation of matrix through their proteolytic/ peptidic and metabolic activity. In both enamel and dentin caries bacterial acid production initiates the processes resulting in caries.…”
Section: Ecological Hypothesis For Dentin and Root Cariesmentioning
confidence: 99%
“…Currently, deterioration can be explained by the activation of endogenous enzymes such as MMPs present in the dentin, most likely due to the acidic properties of the adhesive systems. 34,35 Furthermore, we believe that, in general, the cementing agents used in the present study should not be used directly on the exposed pulp tissue. Although KC can be applied in deep dentin, RU should be preceded by the use of a protective agent on the pulp wall prior to cementation.…”
Section: Discussionmentioning
confidence: 99%